New trends in ophthalmology : medical and surgical management - Boyd, Samuel; Boyd, Benjamin F.; Adamo, Lucas; Akduman, Levent; Alezzandrini, Arturo (Panamá : Jaypee-Highligts Medical Publishers, 2013)
Las nuevas tendencias en oftalmología-manejo médico y quirúrgico "es un volumen oportuno, preciso, clínicamente relevante y extraordinariamente bien ilustrado. Es una excelente fuente de conocimiento clínico actual para los atareados oftalmólogos que se dedican diariamente a cuidar a los pacientes.
New trends in ophthalmology-medical and surgical management" is a timely, accurate, clinically relevant and extraordinarily well ilustrated volume, Its is a superb source of current clinical knowledge for the busy practicing ophthalmologists who are in the trenches caring for patients on a daily basis.
CONTENTS 1. Evaluation and treatment of Ocular surface diseases 2. Pterygium Surgical Management 3. Management of Recurrent Pterygium 4. Dry Eye and Refractive Surgery 5. New Advances in LASIK for the Correction of Low.Moderate Myopia and others ...
Incluye índice
Keywords: CATARATAS (OFTALMOLOGIA); CATARACT -- SURGERY; ENFERMEDADES DE LOS OJOS